4 Pengaruh Faktor Ekonomi Makro Terhadap Harga Saham - Zenita Kurniasari (Jurnal Manajemen Dirgantara, 2019)
This research is aimed to analyze macro factors consist of Inflation Rete, Dolars Kurs, and World Oil Price on Stock Price of Transportation Sub Sectors Listed in Indonesia Stock Exchanges between 2016-2018. As such the goal of this research is to determine the influence of makro economic factors on transportation stock price. The sampels in these research are picked with purposive sampling method with 10 Transportation Company. The analiysis technique used in this research is multiple regression. The partly (t-test) concludes that inflation do not have significant effect on stock price, Kurs have significant effect on stock price in 0.1 significancy level and world oil price have significant effect on stock price with 0.05 significancy level